Edmodo: An Effective Learning Management System Tool for Online Medical Education During COVID-19 Pandemic - Javeria Mansoor; Naila Parveen (ziauddin University, 2024)
Covid-19 is undoubtedly this century's deadliest disease. As the preventive measures for this lethal condition involve minimization of human-to-human contact, physical classes were suspended, and globally the education system continued its function online, the same occurred in medical education. During the pandemic, Learning Management Systems were adopted by various medical institutes and Edmodo was used by most of them due to its cost-effectiveness, versatility, flexible features, user-friendly interface, and self-paced learning. The use of this virtual tool has been welcomed internationally and for developing countries like Pakistan, its use can prove a big aid to medical education in these times of crisis. Among different types of learning management systems, Edmodo has positive feedback from not only students and teachers but it is supportive to administrators as well. Besides helping teachers in sharing lecture materials, and assignments, interacting with students, and conducting quizzes, the scope of its platform can extend to promote critical thinking and conduct flipped classrooms as well. Relevant keywords from 2019-2022 studies were used to retrieve data from "PubMed" and "Google Scholar". It can be concluded that the use of a Learning Management System especially Edmodo for medical education continuation was a need of the hour in the Covid-19 crisis and they are a big aid for teachers. Keywords: Edmodo; Medical Education; Learning Management System.